ASSESSMENT OF GROUNDWATER POTENTIALS OF CRYSTALLINE BASEMENT COMPLEX AQUIFERS USING HYDRAULIC PROPERTIES IN THE USSA AREA OF TARABA STATE, NORTH-EAST NIGERIA - Yohanna, A.; Musa, N.; Balogun, F. O.; Jabbo, J. N.; Adamu, A.; Galumje, S. S. (FUDMA JOURNAL OF SCIENCES, 2022)
Hydrogeological parameters in part of the crystalline Basement Complex rock terrain were characterized using pumping test data. The goal of this research was to determine the aquifer characteristics and groundwater potentials in the area. A total of fifteen (15) wells were used during the investigation. Borehole depths in the studied area range from 40.00 to 45.00 meters. The yield varies from 0.68 l/s to 1.11 l/s. In general, which signify that the yields from wells were low to moderate. Transmissivity (T) ranges from 0.57 to 1.96, with 90 percent of the aquifers having transmissivity between 1.00 and 1.96m2/d and only 10percent of having transmissivity below 1m2/d. data. Transmissivity varies from low to moderate. Borehole-specific capacity ranged from 4.36 to 346 m/day. This cannot sustain a population of 121,500 people based on recommending a basic water requirement of twenty (25) litres per person per day to meet the most basic human needs. When you consider the 121,500 people that rely on these boreholes for their water, it's evident that the aquifers of the borehole have very limited production potential. The area will face a future water crisis if the population continues to expand. Around 196,553 people are expected to live there in near future according National Population Commission (NPC). This is a clear pointer that the area will face portable water crisis except government and other stakeholders involve takes drastic measures.